Shaping Tomorrow's Entrepreneurs: Insights and Innovations from The Erasmus+ Entrepreneurship Training Programme - Melanthiou, Yioula; Triga, Vasiliki; Ferreira Dias, Marta; Amorim, M.; Alves, C.; Gomes, I.; Meireles, G.; Ribeiro, A.L.; Bratitsis, T.; Daubariene, A.; Daunoriene, A.; Ryciuk, U. (My University, 2024)
The Entrepreneurship Training Programme (ETP), funded by the Erasmus+ Programme, is an innovative, short-duration course designed for higher education (HE) students. It aims to cultivate an entrepreneurial mindset and develop skills through the integration of game design and makercentered learning. The development of the ETP involved a rigorous testing process across five European Higher Education Institutions (HEIs), leading to a refined final version accredited for international implementation. During the pilot phase, the ETP was tested in three iterative rounds, engaging 175 students from diverse academic backgrounds and 15 entrepreneurship educators, surpassing initial expectations. The course content, structured around the EntreComp Framework, includes six modules focused on fostering competencies through written assessments, group projects, and practical tasks. The iterative testing process enabled continuous refinement of the course, ensuring its effectiveness and relevance. To evaluate the ETP's impact, a combination of qualitative and quantitative data collection methods was employed. Students maintained learning journals, completed final reflective assignments, and provided feedback through quality surveys. Facilitators also contributed to the evaluation, offering insights for ongoing improvement. Additionally, product pitch evaluations were conducted to assess the practical application of learned skills. The iterative approach of the pilot test involved three rounds, each building on the feedback and outcomes of the previous one. Starting in February 2024, the first round gathered initial feedback and analysis, leading to adjustments for the second round. The final round involved the last phase of training, culminating in a comprehensive evaluation of the programme's overall impact. Feedback from participants indicated high levels of satisfaction and the effectiveness of the programme, with suggestions for incorporating more interactive elements and balancing module content to fit time constraints. This feedback was crucial in shaping the final version of the ETP. The successful pilot testing phase not only exceeded participation goals but also provided invaluable insights for course improvement. The final ETP International course, to be held at the University of Aveiro with participants from all partner countries, is set to establish a robust framework for future international editions. This initiative promises to enhance entrepreneurial education by introducing innovative teaching methodologies, ultimately enriching the educational experience and better preparing students for future challenges.
Keywords: Entrepreneurship Education; Erasmus+ Programme; Higher Education; Entrepreneurial Mindset; Game Design; Maker-Centered Learning; EntreComp Framework